Talkback Smart Mirror Using Magic Mirror and Google Actions - Khan, I; Jyotsna, A; Singh, HV; Rasal, S (International Journal of Computer Sciences and Engineering, 2020)
Smart voice assistants have gained a lot of popularity over the years and have been integrated with numerous devices. This paper aims to focus on the contribution of the voice assistant to ease our lifestyles. Amazon Echo, Google Home are some of the already existing smart assistants. Currently, these systems cannot visualize the results. The main aim of this project is to integrate these assistants with ambient displays, which in turn would lead to increased efficiency, accuracy, and ease of access. The talkback mirror can be used for information retrieval, for conversations, and entertainment of the user. It will cater to the queries of users, without them having to lift a finger.